Estrategia de marketing en el Comercial” Wilmercito S.A.’’ en la parroquia Pimocha del cantón Babahoyo en el periodo 2023. - Mora Manzaba, Marcos Santiago (2025)
The present case study was carried out in the Wilmercito S.A. commercial in the Pimocha parish of the Babahoyo canton where the commercial is dedicated to the sale of groceries and manufacturing products, the main objective is to analyze a marketing strategy that allows increasing the visibility and recognition of the commercial entity, in order to stand out as a business in the area where it is located, the methodology implemented was documentary, and qualitative, quantitative and analytical descriptive methods were used. It was suggested to propose optimal objectives for the respective investigation of the case study, considering key factors in the consistent findings of the commercial and its commercial movements, in order to obtain analytical and quantitative results from the following formulation of the problem, correctly applying an appropriate diagnosis for a conclusion and recommendation of said investigation. It is worth noting that the timely knowledge of new trends in marketing strategies in this type of premises is very high, for this reason many companies are investing a lot in the execution within a point of sale of the products that each company produces to gain better demand and market share.